Durability Aspects of Chemically Stabilized Quarry By-Product Applications in Pavement Base and Subbase. Issue 6 (June 2020) - Qamhia, Issam I. A.; Tutumluer, Erol; Ozer, Hasan; Boler, Huseyin; Shoup, Heather; Stolba, Andrew J.
Recent research conducted at the Illinois Center for Transportation evaluated sustainable applications of quarry by-products (QB) or QB blended with coarse recycled aggregates in chemically stabilized base and subbase layers in flexible pavements and proved that stabilized QB pavement applications show satisfactory pavement performance. This paper investigates the durability aspects of the evaluated QB applications, particularly in relation to freezing–thawing cycles during winter and wetting–drying conditions. Durability tests were conducted on samples extracted from field test sections previously evaluated with accelerated pavement testing (APT) as well as on new samples prepared in the laboratory with the same QB types and material combinations. Field-extracted samples were exposed to multiple cycles of freezing and thawing and wetting and drying throughout APT. Both sets of samples were evaluated by AASHTO T 135 and AASHTO T 136 for wet–dry and freeze–thaw durability, respectively. The results of durability testing indicated that cement-stabilized QB materials benefited from the long-term curing in the field, whereas fly ash-stabilized QB materials were less durable after exposure to multiple freeze–thaw and wet–dry cycles in the field. Field samples compacted at or near the maximum dry density (i.e., having higher relative densities) consistently showed better performance for durability. Further, durability samples made with QB materials from dolomitic aggregate sources, having higher magnesium oxide content in chemical composition, showed better field performances than those with limestone QB having high calcium oxide content. This was possibly linked to cementation observed in the dolomitic QB applications after being exposed to freeze–thaw cycles in three winters.